Valorisation of Tomato Waste as a Source of Cutin for Hydrophobic Surface Coatings to Protect Starch- and Gelatine-Blend Bioplastics - Marta Mroczkowska; David Culliton; Kieran J. Germaine; Manasa Hegde; Edmond F. Tobin; Adriana Cunha Neves (Biomass, 2024)
The valorisation of food by-products is an important step towards sustainability in food production. Tomatoes constitute one of the most processed crops in the world (160 million tonnes of tomatoes are processed every year), of which 4% is waste. This translates to 6.4 million tonnes of tomato skins and seeds. Currently, this waste is composted or is used in the production of low-value animal feed; higher value can be achieved if this waste stream is re-appropriated for more advanced purposes. Plant cuticle is a membrane structure found on leaves and fruit, including tomatoes, and is mainly composed of cutin. The main function of plant cuticle is to limit water loss from the internal tissue of the plant. Cutin, which can be recovered from the tomato skins by pH shift extraction, has hydrophobic (water repellent) properties and is therefore an ideal raw material for the development of a novel water-resistant coating. In this study, biomass-based bioplastics were developed. Unfortunately, although these bioplastics have good mechanical properties, their hydrophilic nature results in poor water barrier properties. To mitigate this, a very effective water-resistant coating was formulated using the cutin extracted from tomato peels. The water vapour permeability rates of the bioplastics improved by 74% and the percentage swelling of the bioplastic improved by 84% when treated with the cutin coating. With physicochemical properties that can compete with petroleum-based plastics, these bioplastics have the potential to address the growing market demand for sustainable alternatives for food packaging. Using ingredients generated from by-products of the food processing industries (circular economy), the development of these bioplastics also addresses the UN’s Sustainable Development Goal (SDG) 12, Sustainable Consumption and Production (SCP).